A survey on packet size optimization for terrestrial, underwater, underground, and body area sensor networks. (6th May 2018) - Yigit, Melike; Yildiz, H. Ugur; Kurt, Sinan; Tavli, Bulent; Gungor, V. Cagri
Summary: Packet size optimization is a critical issue in wireless sensor networks (WSNs) for improving many performance metrics (eg, network lifetime, delay, throughput, and reliability). In WSNs, longer packets may experience higher loss rates due to harsh channel conditions. On the other hand, shorter packets may suffer from greater overhead. Hence, the optimal packet size must be chosen to enhance various performance metrics of WSNs. To this end, many approaches have been proposed to determine the optimum packet size in WSNs. In the literature, packet size optimization studies focus on a specific application or deployment environment. However, there is no comprehensive and recent survey paper that categorizes these different approaches. To address this need, in this paper, recent studies and techniques on data packet size optimization for terrestrial WSNs, underwater WSNs, wireless underground sensor networks, and body area sensor networks are reviewed to motivate the research community to further investigate this promising research area. The main objective of this paper is to provide a better understanding of different packet size optimization approaches used in different types of sensor networks and applications as well as introduce open research issues and challenges in this area. Abstract : In the literature, packet size optimization studies focus on a specific application or deployment environment. However, there is no comprehensive and recent survey paper that categorizes these different approaches. To address this need, in this paper, recent studies and techniques on data packet size optimization for Terrestrial WSNs (TWSNs), Underwater WSNs (UWSNs), Wireless Underground Sensor Networks (WUSNs), and Body Area Sensor Networks (BASNs) are reviewed to motivate the research community to further investigate this promising research area.